Rousseau and the Problem of Human Relations - Warner, John M. (John Martin), 1978- (Book collections on Project MUSE., 2015)
"Investigates the psychological foundations of human sociability as they are treated in the work of Jean-Jacques Rousseau. Argues that Rousseau provides a pessimistic, or tragic, teaching concerning the nature and scope of human connectedness"--Provided by publisher.